Bridging the gap: the challenges of employing entrepreneurial processes within university settings. Issue 5 (2nd September 2016) - Wardale, Dorothy; Lord, Linley
ABSTRACT: In Australia and elsewhere, universities face increasing pressure to improve research output and quality, particularly through partnerships with industry. This raises interesting challenges for academic staff with considerable industry experience who are 'new' to academe. Some of these challenges were faced by the authors who have been successful in generating research, consultancy and executive education funds since joining academe and been somewhat surprised at being described as successful researchers and entrepreneurs. Taking a reflexive look to identify and make explicit our practice through the lenses of social capital and the entrepreneurial process, we identified 10 practices. However, we remain troubled by the dissonance between organisational rhetoric and its rewards for entrepreneurial activities. We offer some considerations for universities to help bridge this gap.